2000
DOI: 10.1177/014107680009300805
|View full text |Cite
|
Sign up to set email alerts
|

A pill in the sandwich: Covert medication in food and drink

Abstract: The covert administration of medicines in food and drink has been condemned by some and condoned by others. We used questionnaires to ascertain the views of people caring for patients with dementia in institutions and in the community. In 24 (71%) of 34 residential, nursing and inpatient units in south-east England, the respondent said that medicines were sometimes given in this way. It was often done secretly and without discussion, probably for fear of professional retribution. Few institutions had a formal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 5 publications
1
51
1
Order By: Relevance
“…As identified in this study, the use of enteral tubes as a route for medicine administration can interfere with nutritional intake either because of the time taken for the medicines to be administered through the tube or because the medicines block the tube. Also, although only alluded to, medicines are hidden in food to aid their administration and, in addition to the ethical issue of the covert administration of medicines [19,[50][51][52], the taste of the food itself may be affected with a negative effect on nutritional intake.…”
Section: Nutritionmentioning
confidence: 99%
“…As identified in this study, the use of enteral tubes as a route for medicine administration can interfere with nutritional intake either because of the time taken for the medicines to be administered through the tube or because the medicines block the tube. Also, although only alluded to, medicines are hidden in food to aid their administration and, in addition to the ethical issue of the covert administration of medicines [19,[50][51][52], the taste of the food itself may be affected with a negative effect on nutritional intake.…”
Section: Nutritionmentioning
confidence: 99%
“…The concealment of medicine in food or beverages is described in non-scientific articles,9 10 and must be a well known practice among carers in nursing homes, but we found only a few scientific papers that report the practice of covert administration. Treloar et al reported that 71% of residential, nursing, and inpatient units in southeast England at least sometimes administered drugs covertly in food and beverages 11. However, the paper did not report how many residents received drugs in this way.…”
Section: Introductionmentioning
confidence: 99%
“…One paper describes how most (71%) residential and nursing-home units in South-East England providing care for people with dementia at least sometimes hide medication in the patients food (Treloar et al, 2000). This paper did not report whether ward characteristics (staffing, ward size, type of ward) or patient characteristics (degree of dementia, ADL function, behavioural function) influenced covert medication.…”
Section: Introductionmentioning
confidence: 99%